English pronunciation in use : elementary : self-study and classroom use - Marks, Jonathan. (Cambridge University Press, 2007)
"English Pronunciation in Use Elementary is for learners of elementary level and above. The material is addressed to the individual learner who may be working alone, but it can also be used in the classroom. This book covers all aspects of pronunciation including individual sounds, word stress, connected speech and intonation. [The book] recognises the importance of pronunciation for listening as well as speaking and learners are provided with both receptive and productive practice."--P. [4] of cover.